Spectrum handoff method by using joint optimization of cumulative delay and channel capacity based on multi-objective PSO - Yupei ZHANG; Zhijin ZHAO; Shilian ZHENG (Dianxin kexue)
At present,a single target optimization function is often used in channel design.While in order to meet the large capacity real-time transmission,it is necessary to consider the cumulative delay and channel capacity simultaneously.The multi-objective function of the target channel design was constructed,and discrete multi-objective particle swarm optimization algorithm(DMOPSO) was proposed to solve it.The discretization design of the population coding and updating was given.The simulation results show that the optimal channel set obtained by proposed spectrum handoff algorithm can take into account the real-time and high throughput of the network,while needing the low complexity.